The Influence of Peers on Student Learning Outcomes of Aqidah Akhlak Learning in Madrasah Ibtidaiyah Muhammadiyah Palak Siring South Bengkulu - Agreliza, Wega; Alimni, Alimni; Zubaidah, Zubaidah (Indonesian Journal of Education and Mathematical Science, 2024)
This study aims to determine the influence of peers on student learning outcomes in Aqidah Akhlak learning at Madrasah Ibtidaiyah Muhammadiyah Palak Siring Bengkulu Selatan, which consists of one class. Researchers took class IV to make a sample of 25 people. The type of research used in this research is quantitative research with a casual associative approach (casual relationship). As for the object of this research is class IV MIM Palak Siring Bengkulu Selatan, totaling 25 people, and data collection techniques through observation, questionnaires, and documentation. It was found that student learning outcomes of management data showed that students' learning outcomes in the high category of Aqidah Akhlak were 3 respondents or 12%. Medium category 18 respondents or 72%. While the low category is 4 respondents or 16%. So it can be concluded that the level of learning outcomes of Aqidah Akhlak students of MIM Palak Siring Bengkulu Selatan is in the medium category, namely 72%. The results of the study can be concluded that there is an influence of peers on student learning outcomes of Aqidah Akhlak at Madrasah Ibtidaiyah Muhammadiyah Palak Siring, South Bengkulu. It can also be proven by the results of calculating the simple linear regression equation Y = 61.25 + 0.235X, which means that for every increase in one variable X (Peer Influence), the value of the Y variable (student learning outcomes) will increase by 26.21 actions, where the influence of peers affect the learning outcomes of Aqidah Akhlak by, 26.21% seen from the performance of the determination coefficient of 73.79%.